Heterosexual Attitudes towards Same-Sex Marriage - Moskowitz, David A. (J Homosex, 2010)
Negative attitudes of heterosexual people toward same-sex marriage relate to the degree to which they are homophobic. However, it has been understudied whether there exists a gender difference in this association. Our results indicated that homophobia was the best predictor of attitudes toward gay male and lesbian marriage, and this was equally true for both heterosexual men and women. However, the attitudinal difference between gay male and lesbian marriage was related to homophobia in men but not in women. That is, for men only, being less homophobic towards lesbians than towards gay men was associated with favoring lesbian over gay men marriage. Considering these results, the role of gender in attitudes toward same-sex marriage seems to be as an important moderator of homophobia.